Influence of Closure & Non-Closure of the Visceral and Parietal Peritoneum on Post Cesarean Morbidity - Tabasi Z.; Abedzadeh M.; Yousefi M. (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Qum, 2010)
AbstractBackground and Objectives: One of the most important issues in promoting mother and child health is reducing the morbidity rate after cesarean section. The aim of this study was to investigate the influence of closure and non-closure of the visceral and parietal peritoneum on post cesarean morbidity in women attending Shabihkhani Maternity Hospital in Kashan, Iran.Methods: This study was conducted with a single blind randomized clinical trial method on 100 parturient women that underwent emergency or elective cesarean section. Patients with previous cesarean section and or abdominal surgery, diseases such as hypertension, diabetes mellitus and premature rupture of membrane and pre operative bleeding, were excluded from this study. Then, the participants were randomly divided into two groups: in one group both peritoneal layers were closed while in the other group, they were not closed. Post operative morbidity including fever, bleeding, post operative pain, analgesic consumption and time of operation were assessed. Data were analyzed with t-tests, and χ2 and a P<0.05 were considered significant.Results: In this study, there were no significant differences between the two groups with respect to age, gestational age, the reason for caesarean section and gravidity, nor were there any differences with respect to the incidence of fever or bleeding and was similar between the two groups, but there was a significant difference between the two groups regarding to feeling of severe pain (P=0.0003), analgesic consumption (P=0.0003) and time of operation (P=0.004). In the non-closure group, dose of analgesic drugs, pain severity and time of operation were less than those of the other group.Conclusion: The Findings showed that non-closure of peritoneal layers as a shorter and simpler procedure has no influence on increasing post cesarean morbidity. Therefore, due to maternal health promotion and early neonatal breastfeeding, non closure of peritoneal layers is recommended.Keywords: Caesarean Section; Pain; Hemorrhage; Bleeding; Peritoneal Clousure.